Situation Report: Hungary, 5 October 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Miners' Strike Settled Quickly, but Key Problems Unresolved / by Karoly Okolicsanyi New Legislation to Encourage Private Enterprise / by Karoly Okolicsanyi Shamir's Visit: Hungary and Israel Closer to Resuming Diplomatic Relations / by Judith Pataki Opponents to Hydroelectrical Project Call for Suspension of Work The Nagymaros Project: Criticism and Support in Austria Parliament Meets to Decide Fate of Hydroelectric Project / by Judith Pataki